Antiproliferative activity of green, black tea and olive leaves polyphenols subjected to biosorption and in vitro gastrointestinal digestion in Caco-2 cells. (October 2020) - Jilani, Hanène; Cilla, Antonio; Barberá, Reyes; Hamdi, Moktar
Graphical abstract: Highlights: Biosorbed digested polyphenols from GT, BT and OL retained their antiproliferation. BF exhibited an antiproliferative activity on Caco-2 cells without cytotoxicity. Antiproliferative action due to arrest in cell cycle S-phase without apoptosis. Biosorbed phenolics in both infusions and suspensions act as cytostatic agents. Abstract: Olive ( Olea europaea L.) leaves and tea ( Camellia sinensis ) are rich sources of bioactive compounds, especially polyphenols. Our previous studies have evidenced the potential use of Saccharomyces cerevisiae as a natural delivery system for these antioxidants and a means to improve their bioaccessibility in the human gut. In the present work, the antiproliferative effect of green tea (GT), black tea (BT) and olive leaves (OL) infusions and suspensions of S. cerevisiae were evaluated, for the first time, in human colon cancer cells (Caco-2) after biosorption and in vitro gastrointestinal digestion. The bioaccessible fractions (BF) were not overtly cytotoxic, not affecting cell viability. ROS and mitochondrial membrane potential changes (Δψm) values were reduced compared with control cells. Moreover, all the BF after biosorption induced a significant (p < 0.05) increase in cell proportions in S-phase. The arrest of the cell cycle was reversible without induction of apoptosis, suggesting that the biosorbed phenolics in both infusions and suspensions act as cytostatic agents.